cos(x)-cos(3x)=0

Simple and best practice solution for cos(x)-cos(3x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for cos(x)-cos(3x)=0 equation:


Simplifying
cos(x) + -1cos(3x) = 0
Multiply cos * x
cosx + -1cos(3x) = 0
Remove parenthesis around (3x)
cosx + -1cos * 3x = 0
Reorder the terms for easier multiplication:
cosx + -1 * 3cos * x = 0
Multiply -1 * 3
cosx + -3cos * x = 0
Multiply cos * x
cosx + -3cosx = 0
Combine like terms: cosx + -3cosx = -2cosx
-2cosx = 0
Solving
-2cosx = 0
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Divide each side by '-2'.
cosx = 0
Simplifying
cosx = 0
The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| 2X+3Y=5.5 | | 5(3y-7)+4y=24 | | Y-34=92 | | (2x-4)+(-5-3x)=0 | | 5/7x-14=-12 | | X^2+7=14 | | 5x-4x+12=14-6 | | (8n+8)+(-4n-4)+(9n+5)= | | y-9x=45 | | 2x-5y=145 | | 7LN(X+4)-6LN(x)= | | z^2+3+4i=0 | | 10+x-6=88 | | 3x(x-7)=9x | | 2w+3=4q | | 4y+3=4-2y(3) | | 4.5x-1.5x=0.3(2-x) | | x^2=y^2+2ad | | 11x+17=88 | | 2x^2-8x-28=0 | | x-3(3x-4)=18 | | (56+24)= | | 4x+3=4-2x(3) | | 6n+27-4n=1 | | 3(2y-10)=4y-7/2 | | c/-15=-28 | | 3x+41=110 | | -50+-72=z | | 3(n+2)=2n+17 | | (4/7)^-1 | | 3.0x-1.5=3+x | | 10x-5=26-3x | | 3(2x-7)=2x+9 | | X/5-9=21 | | x^6-x=0 | | 6+8x=6+x | | .5(8)(4+6)= | | y=5cos-4x | | I=3500(0.11)(69/360) | | 10(x+4)= | | (2.00/3.00)x=7000.00 | | 11/3=4 | | 7x+9=7x+-4 | | X^2-9=6-14x | | f(x)=5x^2-2x+4 | | 7x+9=7k-4 | | x+20+2x=-10-2x-20 | | 9+2*3=4 | | y*-7=28 | | 4(1/2)-2y=b | | 6(7-u)+u=30+4 | | 2x+y=234 | | (6x^2-3x+9)-(x^2+3x-5)= | | X=0.16666666667 | | 9/20-3/20 | | 15+c=25 | | (3-6x)/3=7x-1 | | I=2000(0.15)(61/365) | | 34-79=-25 | | 8x+9y=86 | | 4(2)-2y=b | | 6y-25y=-38+55 | | 2x^2+18x+40x= | | 3g-2h+4g-h+3h= | | (5x-6)(x-8)=(x+6)(1-2x) |


Related pages


what is 10 percent of 2000.00factoring calculator with solution2300-20prime factorization of 120ln19solve derivative calculator15x3what is the gcf of 34 and 8539.99 dollars6x 2x 1the square root of 5295r 5swhat is the lcm of 9ax b solve for xhow to change fractions to decimalsb 2 4acprime factorization of 2543x2 2x 8factorization calculatorfg x calculatorgcf of 90 and 126factor x2-x-124x 2y 20x3 y3 factorprime factorization of 47prime factorization of 9310b107x 4ymultiples of 252prime factorization of 1287yicos arctantan 4x89-100graph 3x y 5quadratic formula solver step by stepalgebra factoring calculator with stepsy 3x 5x 2y 44tanhxsolution of quadratic equation calculatorwhat is the lcm of 4factorise expression calculatorprime factorization 50prime factorization of 360109-50x sinx derivativeln x differentiationsimplify square root of 150x 2y 6 solve for yhcf of 64derivative e 3x96 in roman numeral3x 4y 12 graph2003 roman numerals490.5simplify the square root of 121prime factorization of 280solve cos2x sinx 0prime factorizesolve 3y-2 529 prime factorizationx 2 12x 4 0add and subtract mixed fractions calculator81-19ln2-ln1iy yi yi0.35 as a decimal4x2 5x 62cos 2x-17200s2x 5y 20320-256is239prime factorization of 1898y 2y 3 9107.5 and 97.5quadratics equation solverderivative of 1 tanx9t5secx tanx cotx3y x 6